Standar Proses Pendidikan Nasional: Implementasi dan Analisis terhadap Komponen Guru Matematika di SD Muhammadiyah 027 Batubelah - Restiana, Sri; Agustina, Rahmadatun; Rahman, Jullian; Ananda, Rizki; Witarsa, Ramdhan (MASALIQ, 2022)
This study aims to determine the extent of the implementation of national education process standards in one of the elementary schools located in Kampar District. In addition, this study aims to analyze the components of mathematics teachers related to competence in their performance. This research uses a qualitative approach with a descriptive type. The instruments in this study are the researchers themselves and the performance appraisal questionnaire contains 20 statements with 4 answer choices each. The results showed that in general, SD Muhammadiyah 027 Batubelah has carried out the standards of the educational process properly and continuously, in this case the principle of learning in accordance with government regulations. Another thing obtained from this study is that judging from the performance of mathematics teachers, overall they have excellent performance.